Adult-Onset Case of Undiagnosed Neurodegeneration with Brain Iron Accumulation with Psychotic Symptoms. (20th May 2014) - Attademo, Luigi; Paolini, Enrico; Bernardini, Francesco; Quartesan, Roberto; Moretti, Patrizia
Abstract : Neurodegeneration with brain iron accumulation (NBIA) is a collective term to indicate a group of neurodegenerative diseases presenting accumulation of iron in the basal ganglia. These disorders can result in progressive dystonia, spasticity, parkinsonism, neuropsychiatric abnormalities, and optic atrophy or retinal degeneration. Onset age ranges from infancy to late adulthood and the rate of progression is very variable. So far, the genetic bases of nine types of NBIA have been identified, pantothenate-kinase-associated neurodegeneration (PKAN) being the most frequent type. The brain MRI "eye-of-the-tiger" sign, T2-weighted hypointense signal in the globus pallidus with a central region of hyperintensity, has been considered virtually pathognomonic for PKAN but recently several reports have denied this. A significant percentage of individuals with clinical and radiographic evidence of NBIA do not have an alternate diagnosis or mutation of one of the nine known NBIA-associated genes (idiopathic NBIA). Here we present an adult-onset case of "undiagnosed" NBIA with the brain MRI "eye-of-the-tiger" sign, and with psychotic symptoms which were successfully treated with antipsychotic and mood stabilizer medications. Here, the term "undiagnosed" is used because the patient has not been screened for all known NBIA genes, but only for two of them.